2019
DOI: 10.1111/1556-4029.14153
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Substance Use by Gender Among Participants in a Jail‐Based Substance Use Disorder Treatment Program: 1998–2016

Abstract: Understanding trends in substance use by gender among jail-based treatment program participants can inform policies and programs tailored to this population. Preprogram assessment data from 3509 individuals entering a jail-based substance use disorder treatment program in Missouri between 1998 and 2016 were analyzed. Primary outcome was program participants' strongly preferred substances. Demographic covariates and drug preferences were compared between males and females. Average yearly trends in preferred sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…1 Large-scale data suggest that methamphetamine use and overdose rates have skyrocketed during the last decade. [2][3][4][5][6][7][8] The rising use of methamphetamine and related overdose rates and mortality may be explained in part by the increasing availability, potency, and relative affordability of methamphetamine. 7,[9][10][11] Also contributing to the rise in mortality is the increase in riskier methods of methamphetamine use patterns and diversification of use to populations with greater sociodemographic and mental health risk profiles.…”
Section: Introductionmentioning
confidence: 99%
“…1 Large-scale data suggest that methamphetamine use and overdose rates have skyrocketed during the last decade. [2][3][4][5][6][7][8] The rising use of methamphetamine and related overdose rates and mortality may be explained in part by the increasing availability, potency, and relative affordability of methamphetamine. 7,[9][10][11] Also contributing to the rise in mortality is the increase in riskier methods of methamphetamine use patterns and diversification of use to populations with greater sociodemographic and mental health risk profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated pooled prevalence of drug use disorders was 51% (95% CI = 43–58) for women compared to 30% (95% CI = 22–38) for men (Fazel, Yoon, & Hayes, 2017 ). Another study reviewed trends in substance-use by gender among people in jail over an 18 year period (1998–2016) (Bello, Hearing, Salas, Weinstock, & Linhorst, 2020 ). Significant differences in substance-use trends was noted: Heroin (36.4% women vs. 22.0% men p < 0.0001) and stimulants (38.0% women vs. 19.6% men, p < 0.0001) were more strongly preferred by women than men while alcohol (49.0% men vs. 29.1% women, p < 0.0001) and marijuana (48.7% men vs. 33.6% women, p < 0.0001) were more strongly preferred by men.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences in substance-use trends was noted: Heroin (36.4% women vs. 22.0% men p < 0.0001) and stimulants (38.0% women vs. 19.6% men, p < 0.0001) were more strongly preferred by women than men while alcohol (49.0% men vs. 29.1% women, p < 0.0001) and marijuana (48.7% men vs. 33.6% women, p < 0.0001) were more strongly preferred by men. There was a low overall prevalence for preference of prescription drugs (8.0%), however twice as many women strongly preferred this category compared to men (12.9% women vs. 6.2% men, p < 0.0001) (Bello et al, 2020 ). Other research has shown that women typically begin SUD treatment with more complex and significant physical, emotional and behavioural needs compared to men (Back et al, 2011 ; NIDA., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Often used epidemiological approaches include health or targeted drug surveys (Han et al , 2017; Seitz et al , 2019), treatment admissions registers (Bello et al , 2020; Chhatre et al , 2017), mortality registers (Fugelstad et al , 2019; Lynn et al , 2018) or qualitative studies (Edland-Gryt et al , 2017; van der Poel et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Often used epidemiological approaches include health or targeted drug surveys (Han et al, 2017;Seitz et al, 2019), treatment admissions registers (Bello et al, 2020;Chhatre et al, 2017), mortality registers (Fugelstad et al, 2019;Lynn et al, 2018) or qualitative studies (Edland-Gryt et al, 2017;van der Poel et al, 2009). However, information collected when people enter treatment for substance use appears to be an efficient way to provide insights into the prevalence of substances that may lead to treatment (Montanari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%